Status and risk factors for depression, anxiety, and insomnia symptoms among adolescents in the post-pandemic era - Xing-Jie Yang; Li-Bin Zhang; Lei-Lei Wang; Hu Deng; Yu-Long Li; Rong-Jia Zhao; Jia-Yan Xu; Yu-Chun Yang; Shuang-Jiang Zhou (BMC Public Health)
Abstract Background Owing to their vulnerability to public health crises, adolescents’ mental health status, and related risk factors in the post-pandemic era in China require examination. This study aimed to lay a foundation for subsequent interventions and mental disorder prevention among adolescents. Methods An anonymous online survey was conducted January 8–18, 2023. The survey comprised two parts. The first part collected personal information. The second part included the nine-item Patient Health Questionnaire, seven-item Generalized Anxiety Disorder Scale, and Pittsburgh Sleep Quality Index. Results Of 50,666 adolescent participants, 46.8% displayed depressive symptoms, 31.5% showed anxiety symptoms, and 47.9% experienced difficulties initiating sleep within 30 min, while 4.9% manifested depressive, anxiety, and insomnia symptoms simultaneously. Chi-square tests revealed significant variations in the prevalence of these conditions according to age, sex, coronavirus disease-2019 (COVID-19) infection status, family infection status, and increased screen time (P < 0.001). Logistic regression analysis indicated heightened rates of depression, anxiety, and insomnia symptoms among rural adolescents, females, those aged 16–18 years, individuals with a history of COVID-19, those with a long COVID-19 illness, and those with increased screen time (all P < 0.001). Conclusion The mental health status of adolescents in the post-pandemic era should be taken seriously, particularly that of females, high school students, and adolescents with increased use of electronic screens. Among such efforts, school administrators should strengthen their connection with psychologists, as early identification and intervention in adolescents are important for preventing school crises.